If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4t + -8) = 20 Reorder the terms: (-8 + 4t) = 20 Remove parenthesis around (-8 + 4t) -8 + 4t = 20 Solving -8 + 4t = 20 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 4t = 20 + 8 Combine like terms: -8 + 8 = 0 0 + 4t = 20 + 8 4t = 20 + 8 Combine like terms: 20 + 8 = 28 4t = 28 Divide each side by '4'. t = 7 Simplifying t = 7
| -8n-5n=26 | | 20=-n+6n | | p=15-3Qs | | 910x-12=23 | | -13z+2=-14z+20 | | 24/4x3 | | 2(r+1)-r=-2+4 | | 103x+34=52 | | -3y+4=10 | | .87/1 | | 9/2z-7/3=41/6 | | -5-5j=-4j | | K-14=-18 | | -54=16x+312 | | 4(x+5)=3(x-11) | | (5h+2)=-8 | | 3g-8=-2+2g-10 | | 25=x-16 | | -3h+12=-7h-9-16 | | 9(x-14)=35-7(x+5) | | 24x•35y/25x | | (b+9)=2 | | 14.4=-2.7x-1.8 | | 7p-10=9p+6 | | (3z-3)=9 | | 1.4x-5.6=2.8 | | ax-ab=bx | | 5u=7+6u | | 15-x-9=21 | | 2=11+3a | | 7d-10=8(d-3) | | 4(x+3)=-6(7+5x)+34x |